Object-action dissociation: A voxel-based lesion-symptom mapping study on 102 patients after glioma removal - Pisoni, Alberto (Neuroimage Clin, 2018)
Data concerning the neural basis of noun and verb processing are inconsistent. Some authors assume that action-verb processing is based on frontal areas while nouns processing relies on temporal regions; others argue that the circuits processing verbs and nouns are closely interconnected in a predominantly left-lateralized fronto-temporal-parietal network; yet, other researchers consider that the primary motor cortex plays a crucial role in processing action verbs. In the present study, one hundred and two patients with a tumour either in the right or left hemisphere were submitted to picture naming of objects and actions before and after surgery. To test the effect of specific brain regions in object and action naming, patients' lesions were mapped and voxel-lesion-symptom mapping (VLSM) was computed. Behavioural results showed that left-brain damaged patients were significantly more impaired than right brain-damaged patients. The VLSM showed that these two grammatical classes are segregated in the left hemisphere. In particular, scores in naming of objects correlated with damage to the anterior temporal region, while scores in naming of actions correlated with lesions in the parietal areas and in the posterior temporal cortex. In addition, VLSM analyses carried out on non-linguistic tasks were not significant, confirming that the regions associated with deficits in object and action naming were not generally engaged in all cognitive tasks. Finally, the involvement of subcortical pathways was investigated and the inferior longitudinal fasciculus proved to play a role in object naming, while no specific bundle was identified for actions.